Gut Microbiota Composition Positively Correlates with Sports Performance in Competitive Non-Professional Female and Male Runners - Guy Shalmon; Rawan Ibrahim; Ifat Israel-Elgali; Meitar Grad; Rani Shlayem; Guy Shapira; Noam Shomron; Ilan Youngster; Mickey Scheinowitz (Life)
There is still a pressing need for further investigation to bridge the gap in understanding the differences in gut microbiota composition between female runners and their male counterparts. We aimed to determine the gut microbiota composition in competitive non-professional female and male runners and to correlate the gut bacteria to performance. Our study included 40 subjects, of which 22 were runners (13 males and 9 females) and 18 control subjects (9 males and 9 females, representing the general population who perform light physical activity with a weekly running volume of ≤5 km per week). Fecal specimens were collected and analyzed for taxonomic profiling to compare species’ relative abundances between males and females based on the results of 16SrRNA analysis. Bacterial alpha and beta diversity were assessed to determine the differences in microbial composition between runners and controls, and between sexes. Each participant underwent a maximal oxygen consumption test and a time-to-exhaustion test at 85% of the measured VO2max. Blood lactate was collected every 5 min during the tests. Bacterial alpha diversity showed a significant difference (p = 0.04) between runners and controls. Taxonomic analysis of gut microbiota composition showed a lower Enterobacteriaceae abundance and a higher Methanosphaera abundance in runners compared with the control group. Ten different bacteria (Methanosphaera, Mitsuokella, Prevotellaceae, Megamonas, Rothia, Oscillospira, Bacteroides, Odoribacter, Blautia massiliensis, Butyricicoccus_pullicaecorum) were positively correlated with exercise (VO2max, lactate blood levels, time to exhaustion, and weekly training volume). We found no significant differences in the gut microbiota composition between male and female runners. Gut microbiota composition positively correlates with sports performance in competitive non-professional female and male runners, and female runners show similar gut microbiome diversity to male runners.